Factors Affecting PC and Internet Usage by the Rural Population of Cyprus - Adamides, George; Stylianou, Andreas; Kosmas, Petros C.; Apostolopoulos, Constantinos D. (My University, 2013)
It is widely accepted that the usage of the personal computer and the Internet can improve efficiency in the agricultural sector. Despite the fact that Information and Communication Technologies (ICTs) have evolved rapidly, the farmers are lagging behind in the use of ICTs. This study examines the factors that affect the usage of personal computers and the Internet by Cypriot farmers, by analyzing data from 526 farmers, selected by using the stratified random sampling method. Logit models are used to examine the socioeconomic characteristics of Cypriot farmers that may affect the usage or not, of the personal computer and the Internet. The results showed that 60.6% of them use the personal computer and 54.2% use the Internet. From the analysis of the logit models it was found that the age, the educational level, the income, the type of agricultural activities and the location of the farm, are significant determinants for the personal computer and the Internet usage. Future research is needed to examine the personal computer and Internet applications, their usefulness and the possible benefits for the Cypriot farmers from their usage.
Keywords: logit analysis; Cypriot farmers; PC and Internet usage; ICT